Effect of thermoplastic filling techniques on the push-out strength of root sealing materials - Zigomar Hideo Fecchio Nasser HORIUCHI; Yara Teresinha Correa SILVA-SOUSA; Walter RAUCCI NETO; Fuad Jacob Abi RACHED-JUNIOR; Aline Evangelista SOUZA-GABRIEL; Silvio Rocha Corrêa da SILVA; Edson ALFREDO (Brazilian Oral Research, 2016)
This study evaluates the effect of two thermoplastic obturation systems (MicroSeal and Obtura II) on bond strength of different sealers to intraradicular dentin. Sixty root canals of human canines were prepared using ProTaper rotary files (crown-down technique) and irrigated with 2.5% sodium hypochlorite and 17% EDTA. The root canals were filled by MicroSeal, Obtura II, or lateral compaction techniques using AH Plus and Epiphany SE. 1.5 mm thick root slices were subjected to the push-out test. ANOVA and Tukey's test showed that the bond strength values (MPa) observed in the groups obturated with MicroSeal (2.96 ± 2.72) and Obtura II (2.68 ± 2.18) did not significantly differ from each other (p > 0.05) but were significantly higher than that observed in the group obturated with lateral condensation (2.01 ± 1.48; p < 0.05). There were no statistically significant differences in strength (p > 0.05) among the root canal thirds (cervical: 2.44 ± 2.03; middle: 2.50 ± 2.27; and apical: 2.70 ± 2.34). Adhesive failures were predominant (60%) in all groups. In conclusion, MicroSeal and Obtura II techniques, using AH plus sealer, increased the resistance to displacement of the filling material, when compared with lateral compaction. Moreover, when used with Epiphany SE, these obturation systems did not affect the bond strength of the material to root dentin.